Energy-efficient and self-adaptive routing algorithm based on event-driven in wireless sensor network. (2016) - Zhang, Jing; Yang, Ting; Zhao, Chengli
In wireless sensor networks, the energy consumption is one of the major issues. This paper proposes an event driven based adaptive routing algorithm that avoids the node energy consumption used for emergency monitoring. A cluster tree based on connected dominating set is constructed. When a new event takes place, the algorithm constructs a local topology in that region to quickly transfer the message through a cluster tree, so as to avoid a wide range of flood routing in the network. In addition, it proposes a periodical replacement strategy of the cluster head, which avoids too fast consumption of cluster head node energy. Only the cluster member nodes in a restricted vicinity will change their status. Simulation results show that the proposed approach avoids the node energy consumption used for emergency monitoring and the cluster head can evenly distribute loads, which effectively balances the energy consumption of network nodes, and thus efficiently extends the lifetime of network.